Method for preparing high-compaction high-capacity lithium iron phosphate material by solid-liquid method
High-compacted high-capacity lithium iron phosphate material is prepared by solid-liquid method and graphene sheets are coated on the surface, which solves the problem of decreasing battery capacity and cycle life during high-compact density treatment in the prior art, and achieves efficient electrochemical performance improvement.
Patent Information
- Application Number
- CN202411967956.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
During the high compaction density treatment of existing lithium iron phosphate materials, it is easy to destroy the pores in the battery electrode sheet, resulting in the impermeability of electrolyte and infiltrating, affecting the battery capacity and cycle life.
The solid-liquid method is used to prepare high-pressure high-capacity lithium iron phosphate material. Through ball milling, sand milling, spray drying, sintering and crushing, carbon-coated lithium iron phosphate material is formed, and graphene flakes are uniformly coated on the surface of the material.
It improves the compaction density and discharge specific capacity of lithium iron phosphate materials, extends the cycle life of the battery, and improves the electrochemical performance.
Smart Images

Figure CN119750533A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of methods for preparing positive electrode materials for lithium-ion batteries, and in particular to a method for preparing high-density high-capacity lithium iron phosphate materials by a solid-liquid process. Background Art
[0002] The increasingly severe energy crisis is one of the major challenges facing mankind in the 21st century. In order to meet the growing energy needs of mankind, it is crucial to develop new energy sources that are environmentally friendly and sustainable. Lithium-ion batteries have the advantages of high operating voltage and high energy density, and are the most promising secondary batteries. Lithium iron phosphate, as the positive electrode material of lithium-ion batteries, has the advantages of high capacity, long cycle life, high thermal stability, environmental friendliness, and low cost.
[0003] The compaction density has a great influence on the performance of lithium-ion batteries, and is closely related to the specific capacity, efficiency, internal resistance, and battery cycle performance of the pole piece. Generally speaking, the greater the compaction density, the higher the energy density of the battery can be, so the compaction density is also regarded as one of the reference indicators of the material energy density. In order to further improve the energy density of the lithium-ion battery system, the high compaction density of the lithium iron phosphate material must be increased. At present, when lithium iron phosphate materials are used in lithium-ion batteries, the compaction density of the pole pieces manufactured is generally 2.2-2.3g / cm 3 If high pressure compaction is performed forcibly, the pores in the battery pole piece may be damaged, making it impossible for the electrolyte to penetrate and infiltrate, so that the battery capacity cannot be fully utilized and the cycle life is reduced. Summary of the invention
[0004] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a high-density high-capacity lithium iron phosphate material by a solid-liquid method.
[0005] To this end, an embodiment of the present invention provides a method for preparing a high-density high-capacity lithium iron phosphate material by a solid-liquid method, the method comprising: step S1: mixing an iron source, a lithium source, and a phosphorus source in a certain proportion, adding a certain amount of a carbon source and an additive, ball milling, sand milling, spray drying, and then sintering and crushing at a certain temperature to obtain particles A; step S2: adding a carbon source, a lithium source, and a phosphorus source to the particles A, and then ball milling and sand milling to obtain slurry B; step S3: mixing an iron source, a lithium source, and a phosphorus source in a certain proportion, and adding a certain amount of a carbon source and an additive, and ball milling to obtain slurry C; step S4: slowly adding the slurry C to the slurry B, ball milling to obtain slurry D, spray drying, sintering, and crushing the slurry D to obtain particles E; step S5: adding a certain amount of graphene to the particles E, dispersing them in an N,N-dimethylformamide (DMF) solution, heating and stirring for a certain period of time, and then spray drying, sintering, and crushing to obtain a high-density high-capacity lithium iron phosphate material.
[0006] Preferably, in step S1, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0007] Preferably, in step S1, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particles A being between 0.50% and 0.80%; the additive is one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 1000 and 4000 ppm.
[0008] Preferably, in the step S1, during sand grinding, the sand grinding particle size is controlled to be between 0.40-0.90 μm; the sintering temperature is 700-850° C., and the sintering time is 5-15 hours.
[0009] Preferably, in step S2, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the slurry B being between 1.00% and 1.30%; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide, and the amount of the lithium source added accounts for 0.25-1.00% of the molar ratio of the lithium content in the particle A; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate, and the amount of the phosphorus source added accounts for 0.20-0.50wt% of the mass of the particle A; and the sand grinding particle size is controlled between 0.30-0.80μm.
[0010] Preferably, in step S3, the iron source is one or both of ferrous oxalate and ferrous acetate; the lithium source is one or both of lithium hydroxide and lithium acetate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate. The lithium source, iron source and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0011] Preferably, in step S3, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the slurry C being between 1.00% and 1.30%; the additive is one or more of titanium oxalate, titanium citrate, amino acid chelated titanium, ammonium metavanadate, and magnesium acetate, and the doping amount is controlled between 1000 and 4000 ppm.
[0012] Preferably, in step S4, the time for adding the slurry C to the slurry B is 0.5-1h; the added amounts of the slurry B and the slurry C are in a mass ratio of slurry B:slurry C=[8:2]-[2:8]; the ball milling time is 1-3h; the sintering temperature is 600-800°C, and the sintering time is 5-15h.
[0013] Preferably, in the step S5, the amount of graphene added is 0.50-2.00 wt% of the mass of the particles E; the heating temperature is 150-180° C., and the stirring time is 3-6 h.
[0014] Preferably, in step S5, the sintering temperature is 600-800°C, the sintering time is 5-15h, and the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, so that a high-density and high-capacity lithium iron phosphate material can be obtained.
[0015] The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method provided by the embodiment of the present invention is to first mix the iron source, lithium source, phosphorus source, carbon source and additives, and then perform ball milling and sand milling, spray drying, sintering and crushing to obtain carbon-coated lithium iron phosphate material, and the roundness of carbon-coated lithium iron phosphate material particles is improved. Then add a certain amount of lithium source to supplement the lithium element lost in the first sintering and improve its electrochemical performance; add a certain amount of phosphorus source to reduce the iron-phosphorus ratio, improve the roundness of sintered particles, and improve the particle morphology. Then mix the iron source, lithium source, phosphorus source, carbon source and additives in liquid form to make it easier to coat on the surface of the lithium iron phosphate material, so that it can be regrown and form large micron-sized lithium iron phosphate particles; at the same time, the raw materials of the liquid phase method are easier to form nano-sized small particles, and the liquid additives are easier to disperse in the slurry system. Through sintering, it is easier to perform secondary doping, thereby improving its electrochemical performance. By adding graphene material, graphene flakes are evenly coated on the surface of the lithium iron phosphate material. Among them, graphene flakes diffuse in the mixture under the action of DMF solvent, and are wrapped on the surface of lithium iron phosphate particles through van der Waals interaction. The reversible redox reaction between graphene and lithium ions in the electrolyte can increase the excess capacity, thereby greatly improving the discharge specific capacity of the lithium iron phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A flow chart of a method for preparing a high-density high-capacity lithium iron phosphate material by a solid-liquid method according to an embodiment of the present invention;
[0017] Figure 2 This is a SEM spectrum of the high-density high-capacity lithium iron phosphate material prepared in Example 1 of the present invention;
[0018] Figure 3 This is the XRD spectrum of the high-density high-capacity lithium iron phosphate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0019] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0020] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention provides various specific processes and examples of materials, but those of ordinary skill in the art can appreciate the reusability of other processes and / or the use of other materials.
[0021] The embodiment of the present invention provides a method for preparing a high-density high-capacity lithium iron phosphate material by a solid-liquid method. It should be noted that the high-density high-capacity lithium iron phosphate material in the present invention refers to a material having a compaction density greater than 2.60 g / cm 3 , lithium iron phosphate material with a 0.1C discharge capacity greater than 170 mAh / g. Specifically, Figure 1 As shown, the method includes:
[0022] Step S1: mixing an iron source, a lithium source, and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, ball milling, sand milling, spray drying, and then sintering and crushing at a certain temperature to obtain particles A;
[0023] Wherein, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0024] In an embodiment of the present invention, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particle A being between 0.50% and 0.80%; the additive is selected from one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 1000 and 4000 ppm.
[0025] The sand grinding particle size is controlled between 0.40-0.90μm; in spray drying, the inlet air temperature is 200-220℃, the outlet air temperature is 80-110℃, the blast frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 700-850℃, and the sintering time is 5-15h.
[0026] Step S2: adding a carbon source, a lithium source and a phosphorus source to the particles A, and then ball milling and sand milling to obtain slurry B;
[0027] Among them, the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the slurry B being between 1.00% and 1.30%; the lithium source can be one or more of lithium carbonate, lithium phosphate, and lithium hydroxide, and the amount of the lithium source added accounts for 0.25-1.00% of the molar ratio of the lithium content in the particle A; the phosphorus source can be one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate, and the amount of the phosphorus source added accounts for 0.20-0.50wt% of the mass of the particle A; the sand grinding particle size is controlled between 0.30-0.80μm.
[0028] Step S3: mixing an iron source, a lithium source, and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, and performing ball milling to obtain slurry C;
[0029] The iron source is one or both of ferrous oxalate and ferrous acetate; the lithium source is one or both of lithium hydroxide and lithium acetate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate. The lithium source, iron source and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0030] The carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the slurry C being between 1.00% and 1.30%; the additive is one or more of titanium oxalate, titanium citrate, amino acid chelated titanium, ammonium metavanadate, and magnesium acetate, and the doping amount is controlled between 1000 and 4000 ppm.
[0031] Step S4: slowly adding the slurry C into the slurry B, and obtaining slurry D after ball milling, and spray drying, sintering, and crushing the slurry D to obtain particles E;
[0032] The time for adding the slurry C to the slurry B is 0.5-1h; the amount of the slurry B and the slurry C added is according to the mass ratio of slurry B: slurry C = [8:2]-[2:8]; the ball milling time is 1-3h; in the spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, the blast frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 600-800°C, and the sintering time is 5-15h.
[0033] Step S5: adding a certain amount of graphene to the particles E, dispersing them in a N,N-dimethylformamide (DMF) solution, heating and stirring for a certain period of time, and then spray drying, sintering, and crushing to obtain a high-density high-capacity lithium iron phosphate material.
[0034] The added amount of graphene accounts for 0.50-2.00wt% of the mass of the particle E; the heating temperature is 150-180°C, and the stirring time is 3-6h; in spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, the blast frequency is 80Hz, and the final spray particle size is controlled between D50=20-40μm; the sintering temperature is 600-800°C, and the sintering time is 5-15h; the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm.
[0035] The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method provided by the embodiment of the present invention is to first mix the iron source, lithium source, phosphorus source, carbon source and additives, and then perform ball milling and sand milling, spray drying, sintering and crushing to obtain carbon-coated lithium iron phosphate material, and the roundness of carbon-coated lithium iron phosphate material particles is improved. Then add a certain amount of lithium source to supplement the lithium element lost in the first sintering and improve its electrochemical performance; add a certain amount of phosphorus source to reduce the iron-phosphorus ratio, improve the roundness of sintered particles, and improve the particle morphology. Then mix the iron source, lithium source, phosphorus source, carbon source and additives in liquid form to make it easier to coat on the surface of the lithium iron phosphate material, so that it can be regrown and form large micron-sized lithium iron phosphate particles; at the same time, the raw materials of the liquid phase method are easier to form nano-sized small particles, and the liquid additives are easier to disperse in the slurry system. Through sintering, it is easier to perform secondary doping, thereby improving its electrochemical performance. By adding graphene material, graphene flakes are evenly coated on the surface of the lithium iron phosphate material. Among them, graphene flakes diffuse in the mixture under the action of DMF solvent, and are wrapped on the surface of lithium iron phosphate particles through van der Waals interaction. The reversible redox reaction between graphene and lithium ions in the electrolyte can increase the excess capacity, thereby greatly improving the discharge specific capacity of the lithium iron phosphate material.
[0036] The specific process and effect of the method for preparing high-density high-capacity lithium iron phosphate material by the solid-liquid method of the present invention are further described in detail below in combination with some specific embodiments, but are not limited to the protection scope of the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a high-density high-capacity lithium iron phosphate material by a solid-liquid method, comprising the following steps:
[0039] Step S1: mixing hydroxyferric phosphate with lithium phosphate and phosphoric acid in a molar ratio of Li:Fe:P=1.03:1:1.03, and adding a carbon source mixture consisting of glucose and polyethylene glycol so that the carbon content in particle A is 0.60% and titanium dioxide with a doping amount of 1500ppm to form a mixture; sand-milling the mixture to control the sand-milling particle size to 0.60μm to obtain a nano-sized sand-milling slurry; spray-drying the nano-sized sand-milling slurry to control the air inlet temperature to 220°C, the air outlet temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size D50=20-40μm; placing the spray material in a box furnace and sintering it in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 770°C, and a sintering time of 10h, and then cooling it naturally to obtain a sintered material, and crushing the sintered material through a jet mill to obtain particle A;
[0040] Step S2: Particle A and a carbon source consisting of glucose and polyethylene glycol whose carbon content in slurry B is 1.0% are mixed to form a mixture; lithium carbonate accounting for 0.75% of the lithium content in particle A and phosphoric acid accounting for 0.40wt% of the mass of particle A are added; the mixture is ball-milled and sand-milled to control the particle size of the slurry after sand-milling to be 0.50μm, to obtain slurry B;
[0041] Step S3: ferrous acetate, lithium hydroxide and ammonium dihydrogen phosphate are mixed in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of glucose and polyethylene glycol with a carbon content of 1.10% in slurry C and titanium oxalate with a doping amount of 1500ppm are added to form a mixture; the mixture is ball-milled to obtain slurry C;
[0042] Step S4: Slurry C is slowly added to slurry B through a peristaltic pump, and the adding rate is adjusted to a time of 1 hour, and the ball milling time is controlled to 2 hours to obtain a uniformly mixed slurry D; slurry D is spray-dried, and the air inlet temperature is controlled to be 220° C., the air outlet temperature is 100° C., and the blast frequency is 80 Hz to obtain a spray material with a spray particle size of D50=20-40 μm, and the spray material is placed in a box furnace and sintered in a nitrogen atmosphere, with a heating rate of 3° C. / min, a sintering temperature of 700° C., and a sintering time of 8 hours, and then cooled naturally to obtain particles E;
[0043] Step S5: adding 1.0wt% of graphene to the particles E, dispersing in a DMF solution, stirring for 3h under heating to 180°C, spray drying the particles E, controlling the air inlet temperature to 220°C, the air outlet temperature to 100°C, and the blast frequency to 80Hz, to obtain a spray material with a spray particle size of D50=20-40μm, placing the spray material in a box furnace and sintering it in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 650°C, and a sintering time of 8h; after crushing, the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, and a high-density high-capacity lithium iron phosphate material can be obtained.
[0044] The SEM spectrum of the high-density high-capacity lithium iron phosphate material prepared according to Example 1 is as follows Figure 2 shown.
[0045] The XRD spectrum of the high-density high-capacity lithium iron phosphate material prepared according to Example 1 is as follows Figure 3 shown.
[0046] Example 2
[0047] This embodiment provides a method for preparing a high-density high-capacity lithium iron phosphate material by a solid-liquid method, comprising the following steps:
[0048] Step S1: iron phosphate is mixed with lithium carbonate and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of glucose and polyethylene glycol is added to make the carbon content in particle A 0.80% and titanium dioxide with a doping amount of 1900ppm to form a mixture; the mixture is sand-milled to control the sand-milling particle size to 0.65μm to obtain a nano-sized sand-milling slurry; the nano-sized sand-milling slurry is spray-dried to control the air inlet temperature to 220°C, the air outlet temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 780°C, and a sintering time of 10h, and then naturally cooled to obtain a sintered material, and the sintered material is crushed by a jet mill to obtain particle A;
[0049] Step S2: Particle A and a carbon source consisting of glucose and polyethylene glycol that makes the carbon content in slurry B 1.10% are mixed to form a mixture; lithium carbonate accounting for 1.00% of the lithium content in particle A and phosphoric acid accounting for 0.4wt% of the mass of particle A are added; the mixture is ball-milled and sand-milled to control the slurry particle size after sand-milling to be 0.40μm to obtain slurry B;
[0050] Step S3: ferrous oxalate, lithium hydroxide and phosphoric acid are mixed in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of glucose and polyethylene glycol with a carbon content of 1.10% in slurry C and titanium citrate with a doping amount of 1900 ppm are added to form a mixture; the mixture is ball-milled to obtain slurry C;
[0051] Step S4: Slurry C is slowly added to slurry B through a peristaltic pump, and the adding rate is adjusted to adjust the adding time to 1.0h, and the ball milling time is controlled to 1h to obtain a uniformly mixed slurry D; slurry D is spray-dried, and the air inlet temperature is controlled to 220°C, the air outlet temperature is 100°C, and the blast frequency is 80Hz to obtain a spray material with a spray particle size of D50=20-40μm, and the above-mentioned spray material is placed in a box furnace and sintered in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 750°C, and a sintering time of 6h, and then cooled naturally to obtain particles E;
[0052] Step S5: adding 2.0wt% of graphene to the particles E, dispersing them in a DMF solution, stirring them for 3h under heating to 160°C, spray drying the particles E, controlling the air inlet temperature to 220°C, the air outlet temperature to 100°C, and the blast frequency to 80Hz, to obtain a spray material with a spray particle size of D50=20-40μm, placing the spray material in a box furnace and sintering it in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 700°C, and a sintering time of 8h; after crushing, the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, and a high-density high-capacity lithium iron phosphate material can be obtained.
[0053] Comparative Example 1
[0054] This embodiment provides a method for preparing a lithium iron phosphate material, comprising the following steps:
[0055] Step S1: iron phosphate and lithium carbonate are mixed in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of glucose and polyethylene glycol with a carbon content of 1.25% and titanium dioxide with a doping amount of 1300 ppm are added to form a mixture;
[0056] Step S2: sand-grinding the mixture to control the sand-grinding particle size to 0.70 μm to obtain a nano-sized sand-grinding slurry; spray-drying the nano-sized sand-grinding slurry to control the air inlet temperature to 220° C., the air outlet temperature to 100° C., and the air blast frequency to 80 Hz to obtain a spray material with a spray particle size of D50=20-40 μm;
[0057] Step S3: placing the spray material in a box furnace and sintering it in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 780°C, and a sintering time of 10 hours, and then cooling it naturally to obtain a sintered material, and crushing the sintered material by a jet mill, controlling the air pressure to 0.35 MPa and the classification frequency to 140 Hz, to obtain a crushed material with a particle size of D10>0.35 μm, D50=0.7-1.5 μm, D90<10 μm, and D100<30 μm;
[0058] Step S4: The above crushed materials are further subjected to screening, batching, packaging and other processes to obtain the finished lithium iron phosphate product.
[0059] In order to verify the quality of the finished lithium iron phosphate material prepared by the method for preparing high-density high-capacity lithium iron phosphate material by the solid-liquid method provided in the embodiment of the present invention, the particle size of the high-density high-capacity lithium iron phosphate material prepared in Example 1 was statistically analyzed, and the statistical results are shown in Table 1.
[0060] The lithium iron phosphate material prepared in the above-mentioned Examples 1-2 and Comparative Example 1, the conductive agent carbon black and the binder polyvinylidene fluoride were dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5, and after being evenly dispersed by ball milling, they were coated on aluminum foil and vacuum dried to obtain a positive electrode. The electrolyte is 1 mol / L LiPF6, in which the solvent volume ratio is EC:DMC:EMC=1:1:1, the diaphragm is Celgard polypropylene film, and the metal lithium sheet is the negative electrode, which are assembled together into a button half-cell. The test voltage range is 2.0V-3.75V, and it is charged to 3.75V in a constant current and constant voltage charging mode, and discharged to 2.0V in a constant current discharge mode. The charge and discharge current is 0.1C per cycle, and the test results are shown in Table 2.
[0061] Table 1. Particle size statistics of high-density high-capacity lithium iron phosphate prepared in Example 1
[0062]
[0063]
[0064] Table 2. Test items and test results of Examples 1-2 and Comparative Example 1
[0065] serial number 0.1C first discharge specific capacity (mAh / g) <![CDATA[Compaction density g / cm 3 > Example 1 188.85 2.650 Example 2 183.43 2.655 Comparative Example 1 152.38 2.430
[0066] According to the above examples and control examples and the test results obtained by testing them, the button-type half-cell prepared by the high-density high-capacity lithium iron phosphate material prepared in Example 1 has a significantly improved first charge and discharge capacity at 0.1C compared with that of the control example 1. In addition, the high-density high-capacity lithium iron phosphate material prepared in Example 1 is easier to coat on the surface of the lithium iron phosphate material due to the mixing of the iron source, lithium source, phosphorus source, carbon source and additives in liquid form, and can be regrown to form large micron-sized lithium iron phosphate particles; at the same time, the raw materials of the liquid phase method are easier to form small particles at the nanometer level, and the compaction is improved by matching large and small particles and improving the roundness of the particles; in addition, the liquid additives are easier to disperse in the slurry system, and through sintering, it is easier to perform secondary doping, thereby improving its electrochemical performance. By adding graphene material, graphene flakes are evenly coated on the surface of lithium iron phosphate material. The graphene flakes diffuse in the mixture under the action of DMF solvent and wrap the surface of lithium iron phosphate particles through van der Waals interaction. The reversible redox reaction between graphene and lithium ions in the electrolyte can increase the excess capacity, thereby greatly improving the discharge specific capacity of lithium iron phosphate.
[0067] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method, characterized in that: The method comprises: Step S1: mixing an iron source, a lithium source, and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, ball milling, sand milling, spray drying, and then sintering and crushing at a certain temperature to obtain particles A; Step S2: adding a carbon source, a lithium source and a phosphorus source to the particles A, and then ball milling and sand milling to obtain slurry B; Step S3: mixing an iron source, a lithium source, and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, and performing ball milling to obtain slurry C; Step S4: slowly adding the slurry C into the slurry B, and obtaining slurry D after ball milling, and spray drying, sintering, and crushing the slurry D to obtain particles E; Step S5: adding a certain amount of graphene to the particles E, dispersing them in a N,N-dimethylformamide (DMF) solution, heating and stirring for a certain period of time, and then spray drying, sintering, and crushing to obtain a high-density high-capacity lithium iron phosphate material.
2. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In step S1, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
3. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In step S1, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particles A being between 0.50% and 0.80%; the additive is one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 1000 and 4000 ppm.
4. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In the step S1, the sand grinding particle size is controlled between 0.40-0.90 μm; the sintering temperature is 700-850° C., and the sintering time is 5-15 hours.
5. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In step S2, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the slurry B being between 1.00% and 1.30%; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide, and the amount of the lithium source added accounts for 0.25-1.00% of the molar ratio of the lithium content in the particle A; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate, and the amount of the phosphorus source added accounts for 0.20-0.50wt% of the mass of the particle A; and the sand grinding particle size is controlled to be between 0.30-0.80μm.
6. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In step S3, the iron source is one or both of ferrous oxalate and ferrous acetate; the lithium source is one or both of lithium hydroxide and lithium acetate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. The lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
7. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In step S3, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the slurry C being between 1.00% and 1.30%; the additive is one or more of titanium oxalate, titanium citrate, amino acid chelated titanium, ammonium metavanadate, and magnesium acetate, and the doping amount is controlled between 1000 and 4000 ppm.
8. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In the step S4, the time for adding the slurry C to the slurry B is 0.5-1h; the amount of the slurry B and the slurry C added is based on the mass ratio of slurry B:slurry C=[8:2]-[2:8]; the ball milling time is 1-3h; the sintering temperature is 600-800°C, and the sintering time is 5-15h.
9. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In the step S5, the amount of graphene added is 0.50-2.00wt% of the mass of the particle E; the heating temperature is 150-180°C, and the stirring time is 3-6h.
10. The method for preparing high-density high-capacity lithium iron phosphate material by solid-liquid method according to claim 1, characterized in that: In the step S5, the sintering temperature is 600-800°C, the sintering time is 5-15h; the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, and a high-density and high-capacity lithium iron phosphate material can be obtained.
Citation Information
Cited By
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN121247755A